Live-Cell Assays for Cell Stress Responses Reveal New Patterns of Cell Signaling Caused by Mutations in Rhodopsin, α-Synuclein and TDP-43 - Harlen, Kevin M.; Roush, Elizabeth C.; Clayton, Joseph E.; Martinka, Scott; Hughes, Thomas E. (Frontiers in Cellular Neuroscience, 2019)
Many neurodegenerative diseases induce high levels of sustained cellular stress and alter a number of cellular processes. To examine how different mutations associated with neurodegenerative disease affect cell stress and signaling we created live-cell assays for endoplasmic reticulum (ER)-mediated cell stress and second messenger signaling. We first examined neurodegenerative mutations associated with direct ER stress by exploring the effect of rhodopsin mutations on ER stress and Ca2+ signaling. The rhodopsin P23H mutation, the most common mutation in autosomal dominant Retinitis Pigmentosa, produced increased ER stress levels compared to wild type rhodopsin. Moreover, this increase in cell stress correlated with blunted Ca2+ signaling in a stress dependent manner. Analysis of single cell Ca2+ signaling profiles revealed unique Ca2+ signaling responses exist in cells expressing wild type or P23H rhodopsin, consistent with the idea that second messenger signaling is affected by cell stress. To explore the use of the ER-stress biosensor in neurodegenerative diseases that may not have a direct affect on ER-mediated cell stress we examined how various mutants of ɑ-synuclein and TDP-43 affected ER stress. Mutants of both ɑ-synuclein and TDP-43 associated with Parkinson’s Disease and ALS demonstrated increased ER stress compared to wild type proteins. To examine the effect of ɑ-synuclein and TDP-43 mutants on cellular signaling we created a second live-cell assay to monitor changes in cAMP signaling during expression of various forms of ɑ-synuclein and TDP-43. The increased cell stress caused by expression of the mutant proteins was accompanied by changes in phosphodiesterase activity. Both HEK293T and SH-SY5Y cells expressing these proteins displayed a shift towards increased cAMP degradation rates, likely due to increased phosphodiesterase activity. Together these data illustrate how biosensors for cellular stress and signaling can provide nuanced, new views of neurodegenerative disease processes.